Polycondensation in liquid crystalline phases of nonionic surfactants. Kinetics and morphology - Kumaraswamy, Guruswamy; Wadekar, M. N.; Agrawal, Vikrant V.; Pasricha, R. (Polymer, 2005)
We have investigated acid-catalyzed polycondensation of alkoxysilane monomers in liquid crystalline phases of nonionic CnEm surfactants. The liquid crystalline phase is retained when the monomers polymerize. The high molecular weight molecules formed phase separate from the mesophase and are subsequently organized by it to form micron-sized particles. A variety of particle morphologies are formed by organization of the polymer particles in the mesophase. For condensation of dimethyldimethoxysilane (DMS, with trimethoxysilane, TMS as crosslinker) in hexagonal and lamellar phases, specific reaction conditions, viz. slow condensation kinetics and low crosslink density, give rod-like particles in hexagonal phases and sheet-like structures in lamellar phases. However, when higher acid concentrations are used, the reaction kinetics accelerates and irregular particles form. Irregular particles also form when the fraction of trifunctional crosslinker is increased, and finally complex flower-like structures form for condensation of trimethoxysilane in the hexagonal phase. The particle morphology formed is crucially dependent on the details of the polycondensation rate, crosslinker density and surfactant-monomer/oligomer interactions. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: nonionic; surfactant; templated synthesis

Polymerization in surfactant liquid crystalline phases - Wadekar, M. N.; Pasricha, R.; Gaikwad, A. B.; Kumaraswamy, Guruswamy (Chemistry of Materials, 2005)
We report the formation of cross-linked polysiloxane particles having rodlike and sheetlike morphologies by condensation of monomers in organized liquid crystalline mesophases of nonionic surfactants. The characteristic diffraction pattern obtained from the liquid crystalline surfactant assembly is preserved during polymer synthesis. The polymer colloids are rodlike when synthesized in a hexagonal mesophase and are sheetlike when synthesized in a lamellar mesophase. Interestingly, the size of the polymer particles is on the order of micrometers, viz. 3 orders of magnitude larger than the characteristic size of the surfactant mesophase. Thus, the polymers phase separate from the liquid crystalline phase during polymerization, and organize to resemble the mesophase geometry. The polymer particles are organized so as to minimize the elastic distortion of the surfactant mesophase after they phase separate. We speculate that the observed particle morphologies are formed due to the slow kinetics of polycondensation under our experimental conditions.